Exercise physiologist's role in clinical practice. Issue 2 (2nd December 2008) - Franklin, B; Fern, A; Fowler, A; Spring, T; deJong, A
Abstract : The use of exercise testing has expanded greatly to help guide decisions about medical management and prognosis in a broad spectrum of patients. Numerous epidemiological studies in people with and without documented coronary artery disease have identified a low level of cardiorespiratory fitness as an independent risk factor for all-cause and cardiovascular mortality and that exercise capacity is inversely associated with healthcare costs. Accordingly, unfit men and women should be counselled to exercise in home-based or group preventative or rehabilitative programmes. In the era of managed care, the use of specialised exercise professionals for the supervision of exercise testing and training may represent a safe and cost-effective alternative to many hospitals, clinics and private physician practices. Clinical exercise physiologists (CEPs) can play a critical role in favourably modifying clients' level of cardiorespiratory fitness and physical activity habits. We detail the training of CEPs and outline the clinical settings where they have contributed substantially to healthcare delivery. We also outline the role of registered clinical exercise physiologists. It is important that exercise prescription is not left to a few individuals or small groups. It needs a concerted programme with all those in a position to make a difference actively contributing.